2003
DOI: 10.1093/molehr/gag090
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant enzymatic defences in human follicular fluid: characterization and age-dependent changes

Abstract: The aim of this work was to study the antioxidant enzymatic defences in human follicular fluid and investigate their possible changes during reproductive ageing. To this end, we tested the specific activities and protein expression of enzymes involved in reactive oxygen species (ROS) scavenging and in detoxification of ROS byproducts in follicular fluid from young (range 27-32 years, n = 12) and older (range 39-45 years, n = 12) women participating in an IVF programme. Results show that all the tested enzymes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
134
2
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(149 citation statements)
references
References 27 publications
10
134
2
3
Order By: Relevance
“…An increase in ROS levels, as well as a decline in autophagic markers (LC3-II) in human granulosa cells of older women suggests that there is a decline in reparative autophagy with age leading to granulosa cell apoptosis (Tatone et al 2006, Vilser et al 2010). This result is in concordance with the well-documented, age-related decline in female fertility (Carbone et al 2003, Tatone et al 2006.…”
Section: Ovaries and Testessupporting
confidence: 91%
“…An increase in ROS levels, as well as a decline in autophagic markers (LC3-II) in human granulosa cells of older women suggests that there is a decline in reparative autophagy with age leading to granulosa cell apoptosis (Tatone et al 2006, Vilser et al 2010). This result is in concordance with the well-documented, age-related decline in female fertility (Carbone et al 2003, Tatone et al 2006.…”
Section: Ovaries and Testessupporting
confidence: 91%
“…Furthermore, the expression of antioxidant enzymes in cells that produce steroids (granulosa, thecal and luteal cells) was also reported [42,43]. This suggests that the oocyte is physiologically exposed to oxidative stress and to antioxidant activity both present in the FF [44].…”
Section: Discussionmentioning
confidence: 82%
“…In contrast, GSH and glutathione transferase (GST), which are effective in the removal of free radicals, are reduced in oocytes with age (88). Similarly, Carbone et al demonstrated that follicular fluid from older women exhibited a reduced level of glutathione transferase and catalase activities and a higher level of superoxide dismutase (SOD) activity (89). Taken together, the results indicated that reproductive aging is accompanied by a change in the anti-oxidant enzymatic pattern that could impair ROS scavenging efficiency in the follicular environment.…”
Section: Ovarian Agingmentioning
confidence: 84%